Comparison of different seismic non-linear analyses of an ancient masonry building - Mendes, N. (2009)
This paper presents a study about the possibilities of non-linear static analyses for evaluating the seismic performance of ancient masonry buildings. The adopted case study is a Portuguese typology of the 19th century. Non-linear dynamic and static analyses were carried out using a numerical model calibrated with experimental results obtained in 1:3 reduced scale tests made in a 3D shaking table. In the non-linear dynamic analysis with time integration, the earthquakes are composed by two uncorrelated artificial accelerograms compatible with the elastic response spectrum defined by Eurocode 8. Using this analysis it was verified that the adopted building, with appropriate floor-wall connections, is in the limit of its loading capacity. In the non-linear static analyses (pushover), lateral load distributions proportional to the mass and 1st mode shape in the applicable direction were considered. In an attempt to explore the pushover analyses proportional to the 1st mode shape, adaptive pushover analyses were carried out, in which the load distribution was updated as a function of the existing damage. It is concluded that the pushover analysis does not simulate correctly the failure mode of the structure, namely the out-of-plane mechanism, and should be used with caution.